The Effect of CSR Disclosure to the Firm’s the Cost of Debt: Evidence from Indonesian Companies Listed in Sri-Kehati Index from 2010-2019 - Christina Aprilia Wijaya; Edward Putra Kusuma (iBuss Management, 2021)
Corporate Social Responsibility (CSR) has emerged as one of the most prominent topics in the business world. Consequently, businesses that play a major role in global economic activity are demanded to be socially responsible. This social responsibility behavior must be communicated to maintain effective relationships between firms and stakeholders. Subsequently, sustainability reporting, which focuses on the stakeholders, would give firms a competitive advantage. However, despite the importance of CSR disclosure, most literature only sees the benefits of CSR disclosure from the revenue-outcome instead of cost-related outcome, specifically cost of debt. Thus, this research raises the aforementioned topic to add value and fill the existing literature gap. This research will specifically examine the effect of CSR disclosure to the Cost of debt in the context of Indonesia. The companies which are taken would be listed in the SRI KEHATI Index consecutively from 2010-2019, which data were collected from Bloomberg Database and Annual Report. The results show that ESG Disclosure Score, Environmental Disclosure Score, and Governance Disclosure Score have a negative impact on the Cost of Debt. Meanwhile, Social Disclosure Score has an insignificant impact on the Cost of Debt. Keywords:Corporate Sustainability Responsibility, CSR Disclosure, ESG disclosure, Cost of Debt.